2002
DOI: 10.2298/aci0203101k
|View full text |Cite
|
Sign up to set email alerts
|

Autotransplantacija slezine

Abstract: Auto transplantation of the spleen can be performed in the patients with traumatic rupture of the spleen, in whom spleen could not be conserved in the other way. The right indication for this method is isolated rupture of the spleen (concvasation or complete devascularisation). This method is not recommended in the endangered patients, patients with previous disease of the spleen as well as in the patients with the perforation of the other abdominal organs at the same time. Auto transplantation was performed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 13 publications
2
13
0
Order By: Relevance
“…Like this, there are several publications about spleen autotransplantation in humans 5,7,13,14,15 . Recently, Petroianu and Petronianu 16 related the technique of spleen autotransplantation for the treatment of hypertension portal.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…Like this, there are several publications about spleen autotransplantation in humans 5,7,13,14,15 . Recently, Petroianu and Petronianu 16 related the technique of spleen autotransplantation for the treatment of hypertension portal.…”
Section: Introductionmentioning
confidence: 87%
“…The implant viability is influenced by several factors, such as it size, it forms and place. Several techniques were adopted for the verification of the implants, which could be implanted the whole organ, or a portion as varies from 25 to 50%, or a homogenized tissue form 5,7,8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it has been reported that removal of the spleen causes significantly higher increase of reticulocyte count than other surgeries. This suggests that spleen may somehow hormonally regulate the release of red blood cells into circulation, thus after removal of spleen bone marrow releases more red blood cells as well as more immature erythrocytes into the blood stream (Knežević et al, 2002;Lorber, 1958). Splenectomy also causes changes in number of white blood cells with subsequent leukocytosis (Bessler et al, 2004;Karagülle et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, it is discussed if the viability is superior in the implants of smaller fragments for regenerating in less time than the larger implants 4,5 . As for the location of the implants, several places have been studied: great omentum, peritoneal cavity, splenic store, retroperitoneum, intraportal, abdominal muscle, armpits and subcutaneous of abdominal wall 5,6 .…”
Section: Introductionmentioning
confidence: 99%